Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/opo.12363
|View full text |Cite
|
Sign up to set email alerts
|

Is an objective refraction optimised using the visual Strehl ratio better than a subjective refraction?

Abstract: Purpose To prospectively examine whether using the visual image quality metric, visual Strehl (VSX), to optimise objective refraction from wavefront error measurements can provide equivalent or better visual performance than subjective refraction and which refraction is preferred in free viewing. Methods Subjective refractions and wavefront aberrations were measured on 40 visually-normal eyes of 20 subjects, through natural and dilated pupils. For each eye a sphere, cylinder, and axis prescription was also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 41 publications
5
53
0
Order By: Relevance
“…e results of the current study concerning the VX110 also contrast with other authors that did not report differences in the spherical refraction between the newest wavefront autorefractors and subjective refraction [2,[15][16][17][18]. Nevertheless, some authors reported more negative sphere values with different wavefront aberrometers in comparison with subjective refraction during the last decade [8,32,[34][35][36], coinciding with the results obtained with the VX110 in the current study. No studies assessing the performance of commercial open-field wavefront autorefractors were found in the scientific literature.…”
Section: Discussionsupporting
confidence: 63%
“…e results of the current study concerning the VX110 also contrast with other authors that did not report differences in the spherical refraction between the newest wavefront autorefractors and subjective refraction [2,[15][16][17][18]. Nevertheless, some authors reported more negative sphere values with different wavefront aberrometers in comparison with subjective refraction during the last decade [8,32,[34][35][36], coinciding with the results obtained with the VX110 in the current study. No studies assessing the performance of commercial open-field wavefront autorefractors were found in the scientific literature.…”
Section: Discussionsupporting
confidence: 63%
“…Instrument myopia can be induced with closed-field view of the autorefractometers and whether there is a fogging step used during autorefractometer measurement [ 5 , 6 , 7 ]. Image quality metrics based on the wavefront data is also widely used to optimize the objective refraction and predict the subjective image quality [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The meeting also saw many contributions in the field of wavefront aberrations, such as the work by Hastings et al . that proposed using the visual Strehl visual quality metric to optimize the objective refraction.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…The meeting also saw many contributions in the field of wavefront aberrations, such as the work by Hastings et al 8 that proposed using the visual Strehl visual quality metric to optimize the objective refraction. In myopic subjects these objective refractions led to visual acuities that were equivalent to those obtained by subjective refractions, but the subjects tended to prefer the objective refraction.…”
Section: Where Are We Now?mentioning
confidence: 99%